2013
DOI: 10.3354/meps10134
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in western Hudson Bay ringed seal Phoca hispida diet in relation to environment

Abstract: We present the first study of ringed seal Phoca hispida feeding habits in western Hudson Bay (WHB) using stomach content analysis and stable isotope analysis (SIA). Ringed seals were sampled during 9 Inuit subsistence harvests in Arviat, Nunavut, Canada, over the period 1991 to 2006. During the open-water season in summer and fall, ringed seals fed mostly on sand lance Ammodytes spp. In the spring, when annual sea ice was still present, Arctic cod Boreogadus saida and capelin Mallotus villosus were also import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 76 publications
4
68
0
Order By: Relevance
“…However, the degree of ontogenetic diet and niche shift varied spatially. Our mixing model results revealed that pelagic forage fish, mainly Arctic cod, are the principal prey for both age classes, but that subadults consume more zooplankton than adults, in agreement with previous research (Lowry et al 1980;Bradstreet and Cross 1982;Weslawski et al 1994;Holst et al 2001;Dehn et al 2007;Chambellant et al 2013). In the Arctic, among ringed seal prey items, Arctic cod possesses a higher energy content than zooplankton and crustaceans (24.2 and 12.3-21.1 kJ/g dw −1 , respectively; Weslawski et al 1994) and other pelagic fish such as capelin (21.2 kJ/g dw −1 ; Hedeholm et al 2011) and sand lance (20.1 kJ/g dw −1 ; Anthony et al 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the degree of ontogenetic diet and niche shift varied spatially. Our mixing model results revealed that pelagic forage fish, mainly Arctic cod, are the principal prey for both age classes, but that subadults consume more zooplankton than adults, in agreement with previous research (Lowry et al 1980;Bradstreet and Cross 1982;Weslawski et al 1994;Holst et al 2001;Dehn et al 2007;Chambellant et al 2013). In the Arctic, among ringed seal prey items, Arctic cod possesses a higher energy content than zooplankton and crustaceans (24.2 and 12.3-21.1 kJ/g dw −1 , respectively; Weslawski et al 1994) and other pelagic fish such as capelin (21.2 kJ/g dw −1 ; Hedeholm et al 2011) and sand lance (20.1 kJ/g dw −1 ; Anthony et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…), Themisto libellula, Arctic cod, capelin, sand lance, and sculpin (Bradstreet and Cross 1982;Dehn et al 2007;Chambellant et al 2013). Prey items were collected in 2009-2010 and 2012 via nets and trawls in the summer (June-September) in Resolute and Saglek Bay.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…(Gaston et al, 2012;Chambellant et al, 2013). Rainbow smelt (Osmerus mordax), a temperate species that is expected to thrive in Hudson Bay (Franzin et al, 1994), has also begun to appear in the diet of ringed seals harvested from Arviat (Chambellant et al, 2013). Although the effects that such changes could have on ringed seals are unclear, it has been suggested that climate-related shifts in marine mammal prey communities could lead to nutritional stress caused by limited access to high-quality prey (Bluhm and Gradinger, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Bottom-up processes also appear to be influencing ecosystem dynamics in the Hudson Bay marine environment and changing the feeding ecology of ringed seals and marine birds (Gaston et al, 2012;Chambellant et al, 2013;Young and Ferguson, 2014). Changes in pelagic fish species include a shift from an abundance of Arctic cod (Boreogadus saida) to an increase in sub-Arctic species such as capelin (Mallotus villosus) and sandlance (Ammodytes sp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation